Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Karyawan Di CV 77 Kepindo Sejahtera - Gusdeni Gusdeni; Sundari Sundari; Rinto Alexandro; Hendrowanto Nibel (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
This study aims to determine how the influence of work motivation and work environment that affects employee satisfaction at CV.”77” KEPINDO SEJAHTERA, either partially or simultaneously. The method of this research is to use a questionnaire. Data analysis used multiple linear regression. From the results of the study stated that: (1) Work motivation and work environment simultaneously affect employee satisfaction. (2) Partially, work motivation and work environment affect employee satisfaction significantly. This research approach is a quantitative research with interview data collection techniques, questionnaires, documentation, and observation. Data analysis used multiple linear regression, F statistic test (simultaneous), individual parameter significant test (T test), and R2 determination coefficient test using SPSS 16.0 application. Based on the results of the study using hypothesis testing. In hypothesis testing, SPSS output results with T test results and F test results. The T test output results state that the two variables (X1 and X2) have a significant influence on the variable (Y). The following are the results of X1 against Y getting a significant value of 0.040 <0.05 with the result of T count 2.156 > 2.05183 T table. The results of the X2 T test against Y got a significant value of 0.000 <0.05 with a T count result of 4.877 > 2.05183. Meanwhile, for the SPSS output for testing the F test hypothesis, the significance result is 0.000 < 0.05 with an F count of 72,477 > 3.34. So it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence between Work Motivation (X1) and Work Environment (X2) variables on Job Satisfaction (Y)